Housing Refurbishment for Energy Efficiency and Comfort: Toward sustainable housing in Vietnam - Nguyen, Phan Anh (A+BE | Architecture and the Built Environment, 2021)
The housing stock in Vietnam has boomed in the last few decades, especially in urbanised areas. However, the increasing number of housing units did not go along with housing quality, a healthy living environment or a sustainable building stock. Recent legislation only applies to public buildings but not the private housing sector, which accounts for the majority of the building stock. Therefore, this research aimed to contribute to a more sustainable building stock in Vietnam by improving the energy efficiency in new and renovated urban houses. This research started with examining the energy upgrade potential of the existing houses in Vietnam. Both passive and active refurbishment design measures were investigated for the Vietnamese context. Among the measures, a green facade has a large potential in energy saving. Effect of a green facade on thermal and energy performance was tested by conducting a physical experiment on a real tube house in Hanoi. Next, a stepped design strategy was introduced in a student design workshop in Vietnam. The participants were trained to apply sustainable and energy efficient design measures for Vietnamese tube houses. In addition, the vision for designing future tube houses was discussed on several sustainability aspects: urban densification, energy efficiency, circular economy and social interaction. This research is also expected to contribute to the establishing of a future national technical regulation for private housing in Vietnam.